The effect of the plant density for the yield of the maize hybrids - Pálovics, Balázs; Sárvári, Mihály (Acta Agraria Debreceniensis, 2006)
In order to enchance the yield stability of maize, the effect of plant density on yields was studied on a typical meadow soil in Hajdúböszörmény between 2002-2004. In the plant density experiment, we used the method of Béla Győrffy. The plant densities applied therefore 20 to 100 thousand plants/ha by ten thousand scale. The application of fertilizer rates for the maize hibrids in every year were N: 110 P: 90 K: 120 kg/ha. We used a manual soiling-gun in the experiment. In every year we used plant protection techniques against monocotyledonous and dicotyledonous weeds. The harvest was done by hand. The facts were read by variancie analysis and linear regression analysis. The moisture and the temperatures were extreme in 2002, 2003, 2004. We have to mention defficiery of moisture in 2003 which is shown that the hot days number increased. After evaluating our findings we can conclude that most hybrids showed a significant correlation between increased plant density and the volume of yields. On the basis of the experiments we divided the hybrids into four groups: the first group included the hybrids suitable for increased plant density with a wide range of optimal density values; the second group included hybrids, which did not require high plant density, were capable of good individual performance and tended to grow several ears; the third group included flexible corn types, which grew longer ears in favourable years, thus yielded more; and the fourth group included the hybrids, which were sensitive to increased plant density and which showed a narrow range of optimal density values. Finally, plant density determines the yield; we have to consider optimal plant density intervals as well as optimal plant density, and we also have to place a high emphasis on the use of hybrid-specific technologies.